TINJAUAN MANAJEMEN DIGITALISASI DALAM IMPLEMENTASI REKAM MEDIS ELETRONIK DI RUMAH SAKIT AMC BANDUNG - Desti Wahyu Lestari; Erix Gunawan (LPSDI Bina Patria, 2024)
Digitization management is more complex and includes various aspects. Electronic medical records, digitization or scanning of medical records, and SIMRS are some aspects of digitization management. The purpose of this study was to determine the supporting factors and barriers to digitization management in the implementation of electronic medical records. This research used a descriptive-qualitative method. Interviews were conducted with 6 medical record officers using a questionnaire using the Likert scale method. The results of this study indicate that digitization management in the implementation of electronic medical records at AMC Bandung Hospital has not been fully implemented. Based on the results of the questionnaire calculation using a Likert scale, the result is 10.6%, which implies that digitization management is still very poorly implemented.